Urgent call for the third wish. Issue 1 (8th January 2013) - Roth, Jesse; Holloszy, John O.
Abstract: The people afflicted with obesity and its consequences need a menu of low‐cost programmes to mitigate the over‐nutrition and under‐activity that underlie their condition. This editorial commentary points out the multiple merits (and shortcomings) of the Nordic walking – with ski poles – presented in an accompanying article. The Nordic exercise programme is then examined more broadly in the context of the general principles and limitations of exercise programmes – with and without calorie control – as a guide to future innovations. Copyright © 2013 John Wiley & Sons, Ltd.